Instruction and development in early comprehension of photographs as symbolic objects - Alicia Peralta, Olga; Marcela Salsa, Analía (Anales de Psicología / Annals of Psychology, 2010)
The purpose of this research consisted of studying the impact of instruction in the development of the symbolic comprehension of photographs as sources of information by young children. Three experiments were conducted using a search task. In these experiments the age of the children (24, 30 and 36-months-of-age), the amount (complete, no instruction) and the type (correspondence, intentionality) of the information provided were varied. Results show that at 24 months-of-age children do not comprehend the symbolic function of the photographs in spite of the instructions received. At 30 months-of-age, the information that stressed intentionality turned out to be critical; while the information that stressed correspondences, despite not being enough in itself, provoked that children came to appreciate the symbolic function of pictures during the task, probably as a consequence of a comparison process. Finally, at 36 months-of-age, children captured the symbolic nature of the object with no instruction at all. The results are discussed with regard to the complex relations between development and instruction in early symbolization.